Hadith #4777 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Harith bin Suwayd al-Tymy الحارث بن سويد التيمي; ibn Mas'ud; Ibrahim bin Yazid - Taym al-Rabab إبراهيم بن يزيد بن شريك تيم الرباب; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: If anyone suppresses anger when he is in a position to give vent to it, Allah, the Exalted, will call him on the Day of Resurrection over the heads of all creatures, and ask him to choose any of the bright and large eyed maidens he wishes. Abu Dawud said: The name of the transmitter Abu Marhum is ‘Abd al-Rahman b. Maimun
Grade: Hasan